A second species of Syrraphesina Raffray found adjacent to Wallace's Line(Coleoptera, Staphylinidae, Pselaphinae) - Yin, Zi-Wei; Hlaváč, Peter (Zootaxa, 2020)
The monospecific genus Syrraphesina Raffray, 1903 contains a single species distributed in eastern New Guinea. In this paper a second species from Lombok Island, S. agostii Yin & Hlaváč, sp. nov., is described, figured, and compared to S. pliciventris Raffray, 1903. A revised diagnosis of Syrraphesina is provided. The distribution of Clavigerini through the islands of the world is briefly discussed.